The Effect Of Work-Life Balance On Employee Performance With Mental Health As A Moderating Variable: Penelitian - Sudirman; Ida Farida; Lulu Ulfa Sholihannlisa; Jeni Andriani; Muhammad Nailul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a quantitative research with an explanatory approach. The data used in this study are primary data that researchers obtained from four hundred and twenty-five Sambel Makar employees spread throughout Indonesia. The data used was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypothesis in this article can be proven or not, can be seen carefully in the third table of path coefficients above. The results of the first three rows of the table above indicate that the Work-Life Balance variable can have a positive relationship direction and a significant influence on Employee Performance. This is because the P-Values ​​are positive and below the 0.05 significance level, namely 0.026. These results are in line with research by (Susilo 2024); (NEGA 2020); (PRAMAESTI 2024) & (shafira aida meilia 2024) which show similar results, namely Work-Life Balance can make employees' physical condition stronger, employees happier, and ultimately can improve Employee Performance. In addition, the Mental Health variable can also moderate the influence of the Work-Life Balance variable on Employee Performance due to the same thing, namely the P-Values ​​are positive and below the 0.05 significance level, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven.